Information systems in support of planned social work - Toikkanen, Jenni; Salovaara, Samuel; Lindh, Jari (Finnish Journal of eHealth and eWelfare, 2023)
A systematic and plan-based approach, grounded on the laws governing social work in Finland, frames professional social work, guides the handling of a client’s case and covers several stages from an initial needs assessment to structuring the interventions with present objectives and implementing them in the working phase to the final conclusion of the process. Documentation as a tool for planned social work supports the understanding of the client’s situation, quality work and multidisciplinary cooperation to achieve the objectives set. This article approaches planned social work from the perspective of the information systems and examines their effectiveness in supporting planned social work. The study asked how well the client information systems supported planned social work. Data were collected in the national STePS 3.0 project in autumn 2020, and the responses of licensed social workers (N=429) were selected for the study. The data were analysed using descriptive methods and by constructing summary variables to summarize the data. The quantitative analysis was complemented by a qualitative analysis of data (3,706 words) obtained from the open-ended responses of the participants. According to the findings, social workers rated the quality of information in the information system as mostly good but that it was challenging for most of them to identify the relevant and necessary information. The majority of social workers felt that the information system does not sufficiently support quality work and documentation. Almost half of them also rated support for managing work and understanding the client’s situation as poor. Social workers were most dissatisfied with the ability of the information system to support cooperation and information flow, both between client and professional and at the multidisciplinary and organisational levels. To the best of our knowledge, this is the first study that puts planned social work at the centre of research on information systems. The results can be utilised in the development of information systems and in wellbeing services counties where multidisciplinary cooperation and smooth information flow are emphasised. Social workers’ confidence in the quality of information in the information systems creates a good basis for the utilisation of information; however, further development is needed to ensure that this utilisation takes place in the practice of planned social work.